2011
DOI: 10.1038/onc.2011.514
|View full text |Cite
|
Sign up to set email alerts
|

PEA-15 potentiates H-Ras-mediated epithelial cell transformation through phospholipase D

Abstract: The small GTPase H-Ras is a proto-oncogene that activates a variety of different pathways including the extracellular-signal-regulated kinase mitogen-activated protein kinase (ERK/MAPK) pathway. H-Ras is mutated in many human malignancies and these mutations cause the protein to be constitutively active. PEA-15 blocks ERK-dependent gene transcription and inhibits proliferation by sequestering ERK in the cytoplasm. We therefore investigated whether PEA-15 influences H-Ras mediated transformation. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
2
26
1
Order By: Relevance
“…A previous study reported that PEA15 enhanced the growth of RAS-transformed mouse kidney epithelial cells (45). However, there are many differences between that study and the experiments described here.…”
Section: Discussioncontrasting
confidence: 53%
“…A previous study reported that PEA15 enhanced the growth of RAS-transformed mouse kidney epithelial cells (45). However, there are many differences between that study and the experiments described here.…”
Section: Discussioncontrasting
confidence: 53%
“…PEA15 overexpressed in epithelial cells that express constitutively active Ras is hyperphosphorylated at S116 and the overexpression potentiates Ras-mediated transformation. Interestingly, disruption of the PEA15/PLD1 complex or PLD1 enzyme inhibition with butanol or smallmolecule PLD inhibitors blocks the PEA15 potentiation of Ras-mediated tumorigenesis, suggesting that the PEA15 enhancement of PLD activity in this system drives ERK activation and anchorage-independent growth downstream of Ras (Sulzmaier et al, 2012). These studies strongly suggest that PLD and PtdOH transduce the signals required for Ras-induced oncogenesis, potentially through downstream activation of Raf and the MAPK pathway.…”
Section: B Mitogen-activated Protein Kinasementioning
confidence: 80%
“…This analysis also uncovered a functional signature associated with Ras/MAPK signaling, involving genes including Dusp6, Egr1, and Etv4, and Pld1 (Table 1 and Figure 3C). Notably, this transcriptional program has not been previously ascribed to p63, but may contribute to p63 function in SCC, given that each of these genes has functional links to RAS/MAPK pathway activation in cancer (41,42). A third p63-dependent transcriptional program emerging from this analysis involved genes associated with FGF signaling, including Fgfr2 and Fgfr3 (Table 1 and Figure 3C).…”
Section: Treatment (mentioning
confidence: 94%